Yes, breast cancer related lymphoedema can be managed - Johanna E. Maree (AOSIS, 2011)
The purpose of the study was to demonstrate that breast cancer related lymphoedema can be managed by means of Complete Decompression Therapy and consequently improve quality of life. An instrumental case study design was used. The target population was all women with breast cancer related lymphoedema living in Tshwane, the context of the study. The patient with the most severe breast cancer related lymphoedema treated by the researcher is presented. Mixed methods were used to gather data. The expected 60% limb volume reduction could not be achieved after 4 weeks of induction therapy. After 8.5 weeks of treatment, the limb volume reduced from the initial 3841 mL to 1639 mL, a 57.2% reduction. Patient compliance to compression therapy was a challenge and led to relapse extending the induction phase of treatment. Despite the prolonged treatment, the limb volume reduction improved the patient's quality of life. The study demonstrated and confirmed that despite a degree of noncompliance, breast cancer related lymphoedema can be managed with Complete Decongestive Therapy which, in turn, improves the quality of life of women living with breast cancer. Opsomming Die doelstelling van die studie was om te demonstreer dat borskanker-verwante limfedeem deur middel van Volledige Dekompressie Terapie beheer kan word wat gevolglik die pasiënt se lewenskwaliteit verbeter. 'n Instrumentele gevallestudie-ontwerp is gevolg. Die populasie waaruit die geval gekies is, het uit alle vroue met borskanker-verwante limfedeem in Tshwane, die konteks van die studie, bestaan. Die pasiënt met die ergste limfedeem wat die navorser behandel het, word voorgedra. Gekombineerde metode is ingespan om data in te samel. Die verwagte 60% vermindering in die armedeem binne 4 weke van induksie behandeling is nie bereik nie. Na 8.5 weke van behandeling het die edeem van die oorspronklike 3841 mL tot 1639 mL verminder wat 'n 57.2% reduksie verteenwoordig. Die pasiënt het nie die voorskrifte ten opsigte van dekompressie terapie noukeurig nagekom nie, wat terugvalling en 'n verlengde induksie-fase tot gevolg gehad het. Die vermindering van die armedeem het die pasiënt se lewenskwaliteit nogtans positief beïnvloed. Die studie het aangetoon dat, ten spyte van pasiënt afvalligheid, dit moontlik was om borskanker-verwante limfedeem deur middel van Volledige Dekompressie Terapie te verminder en lewenskwaliteit te verbeter.